Evaluación de técnicas quirúrgicas, ventral y lateral, en la esterilización de caninos hembras. - Amaya García, Katherine Michelle (2021)
The purpose of the research project was to evaluate the surgical techniques, ventral and lateral, in the sterilization of female canines, which allowed a comparison between both techniques in the canine population of San José de Monjas, Quito, checking which is more efficient in recovery. from the patients. The sample consisted of 30 female canines of different sizes, of which a number of 15 dogs underwent each of the ventral and lateral techniques by means of a random selection. Both interventions followed anesthesia, asepsis and surgical protocols, within which the recovery results of both techniques were verified through direct observation. The results of the research showed that the lateral technique is much more beneficial when verifying the operative times 16 ± 5.4 and 21 ± 1.1 min in the lateral technique and conventional methods respectively, while the blood loss was much less in the lateral technique (<2 ml) than in the ventral technique (<8 ml). On the other hand, the total length of the surgical scar was greater in the ventral group (272 ± 176 mm) compared to the group with the lateral technique (202 ± 107.8 mm), while the healing times were 7.07 ± 0.35 and 5.13 ± 0.27 days in the ventral and lateral technique, respectively, so the flank approach is shorter in terms of recovery times.